The effect of a traning program to develop self-confidence and the performance of some basic skills for football beginners between the ages of 14-16 years - Ibrahim, Layth Ismael; Al Saadi, Sanaria Jabbar; Al-Munaem , Firas abd; Ahmed, Omar Saad (International Journal of Psychosocial Rehabilitation, 2020)
The objective of the research (targeted to research to identify the problems facing the player as a result of the lack of self-confidence in the player has a clear impact on the construction of the personality of the player and leads to an imbalance in his performance and skills) • the research community (players emerging youth forum Moqdadya and Khalis Directorate of Youth and Sports Diyala and the number (39) in the Iraqi Ministry of Youth and Sports) The sample of the research and the method of its selection (the sample of the research was formed from the young players of the Youth Forum in Moqdadya Directorate of Youth and Sports of Iraq ,the number of 24 players with the exclusion of goalkeepers. The researchers divided the sample on two experimental and control groups, each group consists of ( 12) Players • The scientific method (the researchers used the experimental approach) • Measuring instruments (self-confidence scales, technical tests for football, observation and experimentation) • Statistical treatments (arithmetic mean, median, standard deviation, torsion factor, Pearson correlation coefficient, T test for independent samples, T test for associated samples) • The results of the research (The use of exercises selected within the training program has a positive impact on the development of self-confidence and the performance of some basic skills of football for the experimental group) • Recommendations of the research (and in light of the findings of the researchers recommend the use of the training program prepared by the researcher in developing self-confidence to other age groups